Process evaluation of the universal access to quality tertiary education act (RA 10931): Status and prospects for improved implementation - Ma. Kristina P. Ortiz; Kris Ann M. Melad; Nina Victoria V. Araos; Aniceto C. Orbeta; Celia M. Reyes (Philippine Institute for Development Studies (PIDS), 2019)
On August 13, 2017, the Philippine government enacted into law the Universal Access to Quality Tertiary Education Act (UAQTE) or Republic Act No. 10931, also known as Free Tuition Law, which mandates all public higher education institutions (HEIs) and government-run technical-vocational institutions (TVIs) to provide free quality tertiary education among eligible Filipino students. This long-awaited policy aims to increase access to tertiary education, particularly for students from poorer households. These goals are intended to be achieved through the implementation of four component programs under the law, namely, (a) free tuition and other school fees in public higher education institutions, (b) free tuition in TESDA technical-vocational training institutes (TVIs), (c) tertiary education subsidy (TES), and (d) student loan program. The study is an early assessment of the RA 10931 during its first year of implementation. Given the limited time and resources, the study concentrated on the implementation of the higher education component and was not able to cover the implementation component on TESDA TVIs. The study investigated the program design and objectives, as specified by the law and its implementing rules and regulations as well as how the these are perceived and understood by key implementing actors. The study also collected initial accounts from key stakeholders and implementers on their experiences in the implementation of the law and the delivery of the policy benefits to intended recipients. The study also examined the organizational and resource requirements for the implementation of the law during this transition period. Finally, the study did an online information gathering and processed available administrative data of pertinent agencies to provide support to information generated from qualitative methods mentioned earlier. [...]
Keywords: 330; tertiary education; free tuition; education subsidy; RA 10931; process evaluation